Generation of the UFM1 Toolkit for Profiling UFM1‐Specific Proteases and Ligases. (2nd October 2018) - Witting, Katharina F.; van der Heden van Noort, Gerbrand J.; Kofoed, Christian; Talavera Ormeño, Cami; el Atmioui, Dris; Mulder, Monique P. C.; Ovaa, Huib
Abstract: Ubiquitin‐fold modifier 1 (UFM1) is a reversible post‐translational modifier that is covalently attached to target proteins through an enzymatic cascade and removed by designated proteases. Abnormalities in this process, referred to as Ufmylation, have been associated with a variety of human diseases. Given this, the UFM1‐specific enzymes represent potential therapeutic targets; however, understanding of their biological function has been hampered by the lack of chemical tools for activity profiling. To address this unmet need, a diversifiable platform for UFM1 activity‐based probes (ABPs) utilizing a native chemical ligation (NCL) strategy was developed, enabling the generation of a variety of tools to profile both UFM1 conjugating and deconjugating enzymes. The use of the probes is demonstrated in vitro and in vivo for monitoring UFM1 enzyme reactivity, opening new research avenues.